Influence of Oxygenation on Granulation in Anaerobic Wastewater Treatment - Soeprijanto Soeprijanto; K. Brighton (ASEAN Journal of Chemical Engineering, 2009)
The emphasis of this study was to put on the ability of bacteria to form granules in anaerobic wastewater treatment. This direction was taken mostly because the success of wastewater treatment in such systems as Upflow Anaerobic Sludge Blanket (UASB) depends on how long the biomass is retained, and this is a function of adhesion of bacteria to reach other to form well-settling granular sludge. The granular sludge will remain in the reactor and will be exposed to the continuous supply of nutrients (wastewater) which is injected into it. The wastewater used in this study was synthetic. It consisted of molasses dissolved in water (100%), and a mixture of molasses and peptone dissolved in water (20 % and 80 %, respectively). Several factors or parameters influence bacteria to form good granules and improve the performance of the digesters. The effects of oxygen on the anaerobes, and the extent to which it acts as an inhibitor or toxic was studied. This was found to be both advantageous and disadvantageous.